A benchmark data set for the mechanical properties of double-stranded DNA and RNA under torsional constraint - Vanderlinden, Willem (Data Brief, 2020)
Nucleic acids are central to the storage and transmission of genetic information and play essential roles in many cellular processes. Quantitative understanding and modeling of their functions and properties requires quantitative experimental characterization. We use magnetic tweezers (MT) to apply precisely calibrated stretching forces and linking number changes to DNA and RNA molecules tethered between a surface and superparamagnetic beads. Magnetic torque tweezers (MTT) allow to control the linking number of double-stranded DNA or RNA tethers, while directly measuring molecular torque by monitoring changes in the equilibrium rotation angle upon over- or underwinding of the helical molecules. Here, we provide a comprehensive data set of double-stranded DNA and RNA under controlled stretching as a function of the linking number. We present data for extension and torque as a function of linking number in equilibrium. We report data for the critical torque of buckling and of the torsional stiffness of DNA and RNA as a function of applied force. Finally, we provide dynamic data for the hopping behavior at the DNA buckling point.